Impacto académico de la modalidad de estudio híbrida "distancia-virtual semipresencial" en la educación superior. Caso carrera de Agroindustria - Bermeo Cobeña, Julexy Angelina (2023)
The new modality of learning has become the main host in the field of education. The objective of this research was to evaluate the academic impact of the blended "virtual-distance" hybrid study modality for the training of students in higher education at the Agroindustry Major. The methodology used was based on a type of descriptive documentary research of in the same way, the methods that were used were the deductive, inductive and analytical-synthetic method. In addition, data collection techniques such as the survey and the interview were used, with which the background and legal framework of the local panorama of the academic impact on the study modality were analyzed, as well as the diagnosis in the learning of the students of the career of Agroindustry and with the results obtained, propose an action plan that allows the strengthening of the academic training of the students of the Agroindustry major in the study modality. It is concluded that in terms of the change in the modality of study it was difficult to be able to adapt both for students and teachers, in the same way, in 37.7% of the respondents it is established that there are significant affectations in their training and student learning. In this way, it is necessary that within the career they have an action plan to redesign the educational system and prioritize students who have low levels of learning and improve the academic experience when these types of changes are presented again.